Development of Online Learning Media through Utilization of the Assure Learning Model on Islamic Law Source Material - Suryanto; Muhajir; Anis Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to find out the PAI learning process that is carried out online as well as measure the effectiveness of online learning media by applying the ASSURE learning model, and to be able to find out the effect of developing online learning media using the ASSURE model in improving student learning outcomes or students' understanding at SMK Negeri 1 Kota. Serang, class X. So that this research produced development products in the form of online learning media which have recently been widely used by educational institutions, especially since the Covid - 19 Pandemic. In this study, the method used was the R&D (Research And Development) research method by adopting the theory of Borg and Gall. The results of this study are an online learning media with the ASSURE model that focuses on PAI subjects on the Sources of Islamic Law in Class X Vocational High School